Critical review of the follow-up protocol for head and neck cancer patients - Kytö E.; Haapio E.; Minn H.; Irjala H. (Cambridge University Press, 2022)
Objective: Head and neck cancer follow-up length, interval and content are controversial. Therefore, this study aimed to evaluate the efficacy of the follow-up protocol after curative treatment in head and neck cancer patients.
Method: Clinical data of 456 patients with new malignancy of the head and neck from a tertiary care centre district from 1999 to 2008 were analysed. Time from treatment, symptoms and second-line treatment outcomes of patients with recurrent disease were evaluated.
Results: A total of 94 (22 per cent) patients relapsed during the 5-year follow-up period; 90 per cent of recurrences were found within 3 years. Fifty-six per cent of the patients had subjective symptoms indicating a recurrence of the tumour. All recurrent tumours found during routine follow-up visits without symptoms were found within 34 months after completion of treatment.
Conclusion: Routine follow up after three years is questionable; recurrent disease beyond this point was detected in only 2 per cent of patients. In this study, all late tumour recurrences had symptoms of the disease. Easy access to extra follow-up visits when symptoms occur could cover the need for late follow up.